A randomized controlled trial of corticosteroids for pain after transoral robotic surgery. (29th August 2017) - Clayburgh, Daniel; Stott, Will; Bolognone, Rachel; Palmer, Andrew; Achim, Virginie; Troob, Scott; Li, Ryan; Brickman, Daniel; Graville, Donna; Andersen, Peter; Gross, Neil D.
Abstract : Objective: To determine if an extended perioperative course of corticosteroids will improve pain control following transoral robotic surgery (TORS). Study Design: Randomized, double‐blind, placebo‐controlled trial. Methods: Patients undergoing TORS for initial treatment of oropharyngeal squamous cell carcinoma received a single intraoperative dose of 10‐mg dexamethasone and then were randomized to receive 8‐mg dexamethasone every 8 hours, or placebo, for up to 4 days after surgery. Pain, measured by visual analog scale (VAS), was the primary outcome measure. Secondary outcome measures included length of stay, dysphagia assessments, and complications. Results: VAS pain scores were similar between steroid and placebo cohorts on postoperative day (POD) 1, 2, and 7 through 21, although they significantly improved in the steroid cohort on POD 3. The steroid cohort also demonstrated a decreased hospital length of stay (median 1 day) and improvement in diet consistency, as measured by the performance status scale on POD 7 through 21. There was no difference in complications between the steroid and placebo cohorts. Conclusion: Extended perioperative corticosteroids after TORS is safe and may allow earlier improvement in diet consistency and decreased length of hospital stay, although postoperative pain appears minimally affected. Level of Evidence: 1b. Laryngoscope, 127:2558–2564, 2017